An iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst and a preparation method thereof

CN122898922APending Publication Date: 2026-10-13NANKAI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610948107.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]RuO2和IrO2是目前酸性OER反应中性能最优异的贵金属电催化剂,其中RuO2具有较高的催化活性,但在酸性条件下的长期稳定性较差,易被氧化溶解;IrO2稳定性优异,但催化活性低于RuO2,且Ir作为稀有贵金属,价格昂贵,大规模应用受到限制

Benefits of technology

[0020]本发明具有的优点和积极效果是:提供一种铱掺杂二氧化钌酸性析氧电催化剂,通过形貌调控剂的作用,在二氧化钌制备过程中构筑微观纳米结构,增大材料比表面积,充分暴露催化活性位点,实现铱均匀掺杂;通过铱掺杂调节二氧化钌电子结构,优化电子传输效率,改善酸性析氧反应动力学,所得催化剂在强酸性条件下具有较佳催化活性与稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898922A_ABST
    Figure CN122898922A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of iridium doped ruthenium dioxide acidic oxygen evolution electrocatalyst and preparation method, soluble ruthenium salt and morphology regulator are mixed in proportion, by pH control, hydrothermal reaction is prepared to obtain ruthenium dioxide matrix, again by soluble iridium salt impregnation doping and high-temperature annealing treatment, the target electrocatalyst is prepared.The catalyst is by constructing micro-nano structure, increase the specific surface area of material, fully expose catalytic active site, realize iridium uniform doping;By iridium doping adjustment ruthenium dioxide electronic structure, optimize electronic transmission efficiency, improve acidic oxygen evolution reaction kinetics, the catalytic activity and stability of the obtained catalyst under strong acidic conditions are obviously superior to pure phase ruthenium dioxide;The catalyst preparation process parameter is controllable, process is stable, equipment requirement is low, is suitable for acidic oxygen evolution reaction, can be widely applied to high-efficiency water electrolysis hydrogen production, carbon dioxide reduction and the like system, with good application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalyst technology, and in particular relates to an iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst and its preparation method. Background Technology

[0002] Proton exchange membrane (PEM) water electrolysis technology has become one of the most promising green hydrogen production technologies due to its advantages such as high operating current density, low ohmic loss, high hydrogen purity, and fast dynamic response. The oxygen evolution reaction (OER) at the anolyte has slow reaction kinetics, requiring highly efficient electrocatalysts to reduce the reaction overpotential and improve energy conversion efficiency. In acidic electrolytes, the harsh conditions of the OER reaction (high proton concentration, strong oxidizing power) place extremely high demands on the stability and activity of the catalyst.

[0003] RuO2 and IrO2 are currently the best-performing noble metal electrocatalysts for acidic OER reactions. RuO2 exhibits high catalytic activity, but its long-term stability under acidic conditions is poor, and it is easily oxidized and dissolved. IrO2 has excellent stability, but its catalytic activity is lower than that of RuO2. Moreover, Ir is a rare and precious metal, and its high price limits its large-scale application. In existing technologies, the synthesis methods of Ir-doped RuO2 catalysts mainly include sol-gel method, impregnation method, and sputtering method, but they have many shortcomings: First, the doping uniformity is poor, and Ir elements are prone to agglomeration, which cannot fully form a solid solution with RuO2, resulting in limited improvement in catalytic activity; second, the catalyst morphology is difficult to control precisely, and the active sites are not sufficiently exposed; third, the synthesis process is complex, the reaction conditions are harsh, and it is difficult to achieve large-scale preparation; fourth, some methods use toxic organic solvents, which are environmentally unfriendly, and the product stability is poor. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides an iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst and its preparation method.

[0005] The technical solution adopted in this invention is: a method for preparing an iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst, the steps of which are as follows:

[0006] Step 1: Mix the ruthenium source solution with the morphology modifier and stir until homogeneous to obtain a precursor mixture solution;

[0007] Step 2: Place the precursor mixture solution in a reaction vessel for hydrothermal reaction. After the reaction is completed, separate and dry to obtain ruthenium dioxide powder;

[0008] Step 3: Prepare ruthenium dioxide powder to form solution A, slowly add iridium source solution dropwise into solution A, stir at constant temperature, centrifuge and dry to obtain iridium-loaded ruthenium dioxide powder;

[0009] Step 4: Iridium-supported ruthenium dioxide powder is placed in an oxidizing atmosphere for heat treatment, and after cooling, iridium-doped ruthenium dioxide electrocatalyst is obtained.

[0010] Preferably, the morphology modifier is one of polyethylene glycol, polyvinylpyrrolidone, and citric acid, and the molar ratio of ruthenium to the morphology modifier is 1:5 to 5:1.

[0011] Preferably, the pH of the precursor mixture is adjusted to 7-9 using an alkaline solution; the alkaline solution is one of potassium hydroxide, sodium hydroxide, potassium carbonate, and ammonia water.

[0012] Preferably, the hydrothermal reaction temperature in step two is 100~200℃, and the reaction time is 1~24h;

[0013] In step three, the constant temperature stirring is carried out in a water bath or oil bath at 40~80℃ for 1~24 hours.

[0014] Preferably, the heat treatment temperature in step four is 200-500℃, and the treatment time is 0.5-4h.

[0015] Preferably, the ruthenium source is one of ruthenium trichloride, ruthenium nitrate, and ruthenium acetate, and the concentration of the ruthenium source solution is 0.001~0.01 mol / L; the iridium source is one of chloroiridic acid, iridium nitrate, and iridium tetrachloride, and the concentration of the iridium source solution is 0~0.1 mol / L; the iridium doping ratio is 1~10 wt% of the mass of ruthenium dioxide.

[0016] An iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst was prepared by a specific method.

[0017] Preferably, it has a rutile structure.

[0018] Application of iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst in acidic water electrolysis for oxygen evolution.

[0019] Preferably, iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst is used as the anode electrode for acidic water electrolysis.

[0020] The advantages and positive effects of this invention are as follows: It provides an iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst. Through the action of a morphology modifier, a micro-nano structure is constructed during the preparation of ruthenium dioxide, increasing the specific surface area of ​​the material, fully exposing catalytic active sites, and achieving uniform iridium doping. By adjusting the electronic structure of ruthenium dioxide through iridium doping, the electron transport efficiency is optimized, and the kinetics of the acidic oxygen evolution reaction are improved. The resulting catalyst exhibits better catalytic activity and stability under strongly acidic conditions.

[0021] The synthesis process uses only deionized water as a solvent, without any toxic organic solvents, making it environmentally friendly and pollution-free. The process steps are simple, the parameters are controllable, and the operation is convenient. It does not require complex equipment and is easy to scale up. The iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst is suitable for acidic oxygen evolution reactions and can be widely used in efficient water electrolysis for hydrogen production, carbon dioxide reduction, and other systems, showing good application potential. Attached Figure Description

[0022] Figure 1 TEM images and EDS mapping images of Ir-RuO2 prepared in Example 1;

[0023] Figure 2 SEM image of RuO2 prepared in Comparative Example 2;

[0024] Figure 3 SEM image of RuO2 prepared in Comparative Example 3;

[0025] Figure 4 LSV performance graphs of Ir-RuO2 prepared in Example 1 and RuO2 prepared in Comparative Example 1;

[0026] Figure 5 LSV performance graph of RuO2 prepared in Comparative Example 2;

[0027] Figure 6 LSV performance graph of RuO2 prepared in Comparative Example 3;

[0028] Figure 7 Electrochemical impedance spectroscopy of Ir-RuO2 prepared in Example 1 and RuO2 prepared in Comparative Example 1;

[0029] Figure 8 Double-layer capacitance diagrams of Ir-RuO2 prepared in Example 1 and RuO2 prepared in Comparative Example 1;

[0030] Figure 9 Electrochemical stability graphs of Ir-RuO2 prepared in Example 1 and RuO2 prepared in Comparative Example 1;

[0031] Figure 10 LSV performance graph of 5wt% Ir-doped RuO2;

[0032] Figure 11 Electrochemical stability diagram of 5wt% Ir-doped RuO2. Detailed Implementation

[0033] The embodiments of the present invention will now be described with reference to the accompanying drawings.

[0034] This invention relates to an iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst and its preparation method. A soluble ruthenium salt and a morphology modifier are mixed in a specific ratio, and a ruthenium dioxide matrix is ​​prepared through pH adjustment and hydrothermal reaction. The target electrocatalyst is then obtained through soluble iridium salt impregnation doping and high-temperature annealing. By optimizing the iridium source impregnation doping process, the defects of disordered catalyst morphology, uneven iridium doping, and chaotic distribution of active sites in traditional preparation processes are overcome. This method achieves low-load, uniform iridium doping while ensuring catalytic performance, effectively reducing the proportion of precious metal iridium used and significantly reducing catalyst preparation costs.

[0035] The specific preparation method of iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst is as follows:

[0036] Step 1: Mix the ruthenium source solution with the morphology modifier and stir until homogeneous to obtain a precursor mixed solution; wherein, the ruthenium source is one of ruthenium trichloride, ruthenium nitrate and ruthenium acetate, with a concentration of 0.001~0.01 mol / L; the morphology modifier is one of polyethylene glycol, polyvinylpyrrolidone and citric acid, and the molar ratio of ruthenium element to morphology modifier is 1:5 to 5:1;

[0037] Furthermore, the pH value of the precursor mixture solution can be adjusted by using an alkaline solution, including but not limited to one of potassium hydroxide, sodium hydroxide, potassium carbonate, and ammonia water, to adjust the pH of the system to 7-8;

[0038] Step 2: Place the precursor mixture solution in a reaction vessel, and place the reaction vessel in an oven for hydrothermal reaction. The heating rate of the hydrothermal reaction is 1~10℃ / min, the reaction temperature is 100~200℃, and the reaction time is 1~24h, preferably 160℃ and 12h. After the reaction is completed, let the reaction system cool to room temperature, then centrifuge at 8000~12000r / min for 5~10min / time. The obtained product is ultrasonically cleaned with ultrapure water or ethanol for 1~5min. After drying, ruthenium dioxide powder is obtained.

[0039] Step 3: Prepare solution A by dissolving ruthenium dioxide powder. The iridium source is one of chloroiridium acid, iridium nitrate, or iridium tetrachloride, and the concentration of the iridium source solution is 0~0.1 mol / L. Slowly add the iridium source solution dropwise into solution A. The doping ratio (based on iridium) is 1~10 wt% of the ruthenium dioxide mass. Maintain a constant temperature and stir at 40~80℃ using a water bath or oil bath for 1~24 h, preferably 12 h. After stirring, centrifuge at 8000~12000 r / min for 5~10 min / time. The resulting material is ultrasonically cleaned using ultrapure water or ethanol for 1~5 min. After drying, obtain iridium-loaded ruthenium dioxide powder.

[0040] Step 4: Place the iridium-supported ruthenium dioxide powder in an oxidizing atmosphere and heat-treat it by heating. The oxidizing atmosphere is air. The heating rate of the heat treatment is 1~10℃ / min, the heating temperature is 200~500℃, and the holding time is 0.5~4h. Preferably, the heating rate is 2℃ / min, the heating temperature is 300℃, and the holding time is 2h. After the heat treatment is completed and cooled, the iridium-doped ruthenium dioxide electrocatalyst is obtained.

[0041] A combined hydrothermal reaction and impregnation-annealing method was employed to first prepare pure-phase spherical RuO2, followed by impregnation to achieve uniform Ir loading. Subsequent annealing allowed Ir to fully integrate into the RuO2 lattice, forming a stable solid solution structure. This method solved the problems of uneven Ir doping and easy agglomeration in existing technologies, significantly improving the catalytic activity and stability of the catalyst. By controlling the morphology of RuO2, molecules were uniformly coated on the entire crystal surface through coordination adsorption of Ru(OH)3 precursor colloids via ether-bonded oxygen. A three-dimensional hydration steric barrier was constructed to uniformly limit the ion deposition rate on each crystal facet, eliminating the anisotropic preferential growth trend of the crystal and guiding the precursor to grow at a constant rate in three dimensions to form spherical primary particles. This increased the exposure of active sites, improved catalyst dispersibility, and inhibited catalyst agglomeration. The iridium-doped ruthenium dioxide electrocatalyst prepared by the above method exhibited a rutile structure.

[0042] The prepared iridium-doped ruthenium dioxide electrocatalyst can be used as the anode electrode in acidic water electrolysis, meeting the requirements of proton exchange membrane water electrolysis technology for a wide current density adaptability and long-life catalyst. Furthermore, this preparation method avoids the problem of excessive iridium doping, precisely controlling various synthesis parameters, significantly reducing the amount of Ir used, lowering catalyst costs, and simultaneously maintaining both catalytic activity and stability, exhibiting excellent performance in acidic OER reactions. Iridium-doped ruthenium dioxide electrocatalysts possess advantages such as low overpotential, high catalytic activity, and high stability in acidic electrolytes, making them suitable for hydrogen production through water electrolysis and possessing significant industrial application value.

[0043] The present invention will now be described with reference to the accompanying drawings. Experimental methods not specifically described in terms of operation steps are performed in accordance with the corresponding product manuals. Unless otherwise specified, the instruments, reagents and consumables used in the embodiments can be purchased from commercial companies.

[0044] Example 1:

[0045] Precursor mixing and morphology control: 0.001 mol of ruthenium chloride trihydrate precursor was placed in a polytetrafluoroethylene (PTFE) liner, and 60 mL of deionized water was added. The mixture was magnetically stirred for 30 min until completely dissolved. Then, 0.2 g of polyethylene glycol (PEG-8000) with a molecular weight of 8000 was added, and stirring was continued for 45 min until the system was homogeneous. A 1 mol / L NaOH solution was slowly added dropwise to the mixture while stirring, and the pH was adjusted to 8.5. The PTFE liner containing the mixture was sealed in a stainless steel reactor, which was then placed in an oven and heated to 180 °C at a rate of 10 °C / min. The temperature was maintained for 12 h, and after the reaction, the mixture was allowed to cool naturally to room temperature. The first stage of centrifugation, washing and drying: The cooled reaction system was transferred to a centrifuge tube and centrifuged at 10,000 r / min for 3 min. The centrifugation washing order was deionized water, ethanol and deionized water, and the washing was repeated 3 times. After washing, the product was placed in a vacuum oven and dried at 60℃ for 12 h. After cooling to room temperature, RuO2 powder sample was obtained.

[0046] Ir doping and annealing: 100 mg of the above RuO2 powder was placed in a beaker, 10 mL of deionized water was added, and the mixture was magnetically stirred for 45 min until fully dispersed to obtain solution A; 10.8 mg of anhydrous chloroiridium acid (H2IrCl6) was dissolved in 10 mL of deionized water and magnetically stirred for 25 min until completely dissolved to obtain solution B; solution B was slowly added dropwise to solution A while stirring continuously for 50 min until uniformly mixed, and then the beaker was placed in a water bath and heated at 50 °C for 12 h; after the reaction was completed, the mixture was centrifuged at 10000 r / min for 5 min, and washed three times in the order of deionized water, ethanol, and deionized water, and then placed in a vacuum oven and dried at 60 °C for 12 h, and cooled to room temperature to obtain the Ir-loaded RuO2 powder sample.

[0047] Annealing treatment: The above powder sample was placed in an alumina crucible and then placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 300°C at a heating rate of 2°C / min, and annealed for 2 hours. The sample was then naturally cooled to room temperature to obtain an iridium-doped ruthenium dioxide high-efficiency acidic oxygen evolution electrocatalyst.

[0048] The prepared catalyst was analyzed, and the transmission electron microscope (TEM) image is shown below. Figure 1 As shown, the catalyst has a spherical morphology, and the Ir element is relatively uniformly dispersed as confirmed by the EDS mapping diagram.

[0049] Comparative Example 1:

[0050] Precursor mixing and morphology control: 0.001 mol of ruthenium chloride trihydrate precursor was placed in a polytetrafluoroethylene liner, and 60 mL of deionized water was added. The mixture was magnetically stirred for 30 min until completely dissolved. Then, 0.15 g of polyethylene glycol with a molecular weight of 8000 was added, and stirring was continued for 30 min until the system was homogeneous. The pH of the system was adjusted to 8.5 using a 1 mol / L NaOH solution. The reactor was placed in an oven and heated to 180 °C at a rate of 10 °C / min, and the reaction was maintained at this temperature for 12 h. The mixture was then allowed to cool naturally to room temperature. First stage centrifugation, washing, and drying: The mixture was centrifuged at 10000 r / min for 10 min, and washed three times in the order of deionized water, ethanol, and deionized water. The mixture was then placed in a vacuum oven and dried at 60 °C for 12 h to obtain a pure phase RuO2 powder sample.

[0051] The RuO2 powder sample was placed in an alumina crucible and then placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 300°C at a heating rate of 2°C / min, and the mixture was held at that temperature for 2 hours. After natural cooling to room temperature, the ruthenium dioxide electrocatalyst was obtained.

[0052] Comparative Example 2:

[0053] 0.001 mol of ruthenium chloride trihydrate precursor was placed in a polytetrafluoroethylene liner, and 60 mL of deionized water was added. The mixture was magnetically stirred for 30 min until completely dissolved. The pH of the system was adjusted to 9 using a 1 mol / L NaOH solution. The reactor was placed in an oven and heated to 180 °C at a rate of 5 °C / min, and the reaction was maintained at this temperature for 12 h. The mixture was then allowed to cool naturally to room temperature. The first stage involved centrifugation, washing, and drying: the mixture was centrifuged at 10000 r / min for 10 min, and washed three times in the order of deionized water, ethanol, and then deionized water. The mixture was then placed in a vacuum oven and dried at 60 °C for 12 h to obtain a pure phase RuO2 powder sample.

[0054] The RuO2 powder sample was placed in an alumina crucible and then placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 300°C at a heating rate of 5°C / min, and annealed for 2.5 hours. The sample was then naturally cooled to room temperature to obtain the ruthenium dioxide electrocatalyst.

[0055] The prepared catalyst was analyzed, and the scanning electron microscope (SEM) image is shown below. Figure 2 As shown, due to the absence of morphology modifiers, the catalyst exhibits a plate-like morphology with varying sizes.

[0056] Comparative Example 3:

[0057] 0.001 mol of ruthenium chloride trihydrate precursor was placed in a polytetrafluoroethylene liner, and 60 mL of deionized water was added. The mixture was magnetically stirred for 30 min until completely dissolved. Then, 0.3 g of polyethylene glycol with a molecular weight of 8000 was added, and stirring was continued for 60 min until the system was homogeneous. The reactor was placed in an oven and heated to 160 °C at a rate of 5 °C / min, and the reaction was maintained at this temperature for 18 h. The mixture was then allowed to cool naturally to room temperature. The first stage involved centrifugation, washing, and drying: the mixture was centrifuged at 10000 r / min for 10 min, and washed three times in the order of deionized water, ethanol, and deionized water. The mixture was then placed in a vacuum oven and dried at 60 °C for 12 h to obtain a pure phase RuO2 powder sample.

[0058] The RuO2 powder sample was placed in an alumina crucible and then placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 300°C at a heating rate of 5°C / min, and annealed for 2.5 hours. The sample was then naturally cooled to room temperature to obtain the ruthenium dioxide electrocatalyst.

[0059] The prepared catalyst was analyzed, and the scanning electron microscope (SEM) image is shown below. Figure 3 As shown, due to the lack of pH adjustment of the precursor mixture solution, a regular RuO2 structure could not be formed, and the catalyst exhibited an irregular morphology.

[0060] Example 2:

[0061] The catalysts prepared in Example 1 and Comparative Example 1 were used as anode catalysts and electrolyzed in an acidic electrolyte medium to evaluate their oxygen evolution reaction (OER) performance. The specific test procedure is as follows:

[0062] Linear sweep voltammetry (LSV) was selected, using an electrochemical workstation as the power source. 5 mg each of the iridium-doped ruthenium dioxide catalyst (Ir-RuO2) prepared in Example 1 and the ruthenium dioxide catalyst (RuO2) prepared in Comparative Example 1 were weighed using a balance and dissolved in a mixed solution of 650 μL isopropanol and 300 μL water. 50 μL of 5% wt Nafion solution was added, and the mixture was ultrasonicated until uniformly dispersed. The solution was sprayed onto a conductive carbon paper substrate as the anode (i.e., the working electrode) using a spray gun. A three-electrode system (Ag / AgCl as the reference electrode and a platinum sheet as the counter electrode) was used to test the oxygen evolution reaction (OER) performance of the Ir-RuO2 catalyst prepared in Example 1 and the RuO2 catalyst prepared in Comparative Example 1 in 0.5 M H2SO4 aqueous solution. The LSV scan rate was set to 5 mV / s. The obtained electrochemical test curves are shown below. Figure 4 As shown. By Figure 4 It can be seen that, comparing Example 1 (Ir-RuO2) and Comparative Example 1 (RuO2), the Ir-RuO2 catalyst at 10 mA / cm 2The required overpotential at the current density is the lowest, at 186 mV, lower than RuO2's 208 mV. Meanwhile, at the same potential, Ir-RuO2 exhibits a significantly higher oxygen evolution catalytic current density, indicating that Ir doping significantly regulates the surface and interface electronic structure of RuO2, thereby enhancing its electrocatalytic activity.

[0063] The catalysts prepared in Comparative Examples 2 and 3 were used as anode catalysts and electrolyzed in an acidic electrolyte medium to evaluate their oxygen evolution reaction (OER) performance; Figure 5 As shown, the catalyst in Comparative Example 2 has a capacity of 10 mA / cm². 2 The corresponding overpotential is 409mV, such as Figure 6 As shown, the catalyst in Comparative Example 3 has a capacity of 10 mA / cm². 2 The corresponding overpotential is 515mV; the electrocatalytic activity of the catalysts prepared in Comparative Examples 2 and 3 is not only significantly lower than that of the catalyst in Example 1, but also significantly lower than that of the catalyst prepared in Comparative Example 1.

[0064] The interfacial charge transport behavior of the catalytic materials in Example 1 and Comparative Example 1 was analyzed by electrochemical impedance spectroscopy. The results are as follows: Figure 7 As shown, the Ir-RuO2 catalyst exhibits the lowest charge transfer impedance, indicating that Ir doping can improve the electron transport performance of RuO2 and promote interfacial charge transfer during the acidic oxygen evolution reaction.

[0065] The electrochemical active area of ​​the catalytic materials in Example 1 and Comparative Example 1 was characterized by double-layer capacitance analysis. Cyclic voltammetry tests were performed at different scan rates within the non-Radial interval, and the double-layer capacitance was calculated based on the linear relationship between the current density difference and the scan rate. The results are as follows: Figure 8 As shown, the Ir-RuO2 catalyst has a larger double-layer capacitance, indicating that Ir doping makes the RuO2 surface rougher and creates a composite catalytic layer with more accessible active sites.

[0066] The stability of the catalysts in Example 1 and Comparative Example 1 was investigated. A constant current method was used to record the voltage changes provided by the electrochemical workstation while maintaining a specific current density. The stability test results are as follows: Figure 9 As shown in the figure, the voltage of the Ir-RuO2 catalyst remained almost unchanged under constant current conditions, exhibiting smaller voltage decay and a more stable potential curve, indicating a significant improvement in its structural stability and resistance to dissolution. In contrast, the RuO2 catalyst showed a significant voltage increase during operation, indicating that its active centers gradually deactivated and its stability was slightly worse.

[0067] The comparison shows that the Ir-RuO2 catalyst outperforms the RuO2 catalyst in all aspects, and the Ir doping strategy can effectively enhance the acidic oxygen evolution catalytic activity and stability of RuO2.

[0068] Example 3

[0069] Precursor mixing and morphology control: 0.001 mol of ruthenium chloride trihydrate precursor was placed in a polytetrafluoroethylene (PTFE) liner, and 60 mL of deionized water was added. The mixture was magnetically stirred for 30 min until completely dissolved. Then, 0.2 g of polyethylene glycol (PEG-8000) with a molecular weight of 8000 was added, and stirring was continued for 30 min until the system was homogeneous. A 1 mol / L NaOH solution was slowly added dropwise to the above mixture while stirring, and the pH of the system was adjusted to 9. The PTFE liner containing the system was sealed in a stainless steel reactor, and the reactor was placed in an oven. The temperature was increased to 160 °C at a rate of 10 °C / min, and the reaction was maintained at this temperature for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The first stage of centrifugation, washing and drying: The cooled reaction system was transferred to a centrifuge tube and centrifuged at 10,000 r / min for 3 min. The centrifugation washing order was deionized water, ethanol and deionized water, and the washing was repeated 3 times. After washing, the product was placed in a vacuum oven and dried at 60℃ for 12 h. After cooling to room temperature, RuO2 powder sample was obtained.

[0070] Ir doping and annealing: 100 mg of the above RuO2 powder was placed in a beaker, 10 mL of deionized water was added, and the mixture was magnetically stirred for 45 min until fully dispersed to obtain solution A; 5.4 mg of anhydrous chloroiridium acid (H2IrCl6) was dissolved in 10 mL of deionized water and magnetically stirred for 25 min until completely dissolved to obtain solution B; solution B was slowly added dropwise to solution A while stirring continuously for 30 min until uniformly mixed, and then the beaker was placed in a water bath and heated at 50 °C for 6 h; after the reaction was completed, the mixture was centrifuged at 10000 r / min for 5 min, and washed three times in the order of deionized water, ethanol, and deionized water, and then placed in a vacuum oven and dried at 60 °C for 24 h, and cooled to room temperature to obtain the Ir-loaded RuO2 powder sample.

[0071] Annealing treatment: The above powder sample was placed in an alumina crucible and then placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 350°C at a heating rate of 5°C / min, and annealed for 2 hours. The sample was then naturally cooled to room temperature to obtain an iridium-doped ruthenium dioxide electrocatalyst.

[0072] The above catalyst was used as the anode catalyst and electrolyzed in an acidic electrolyte medium to evaluate its oxygen evolution reaction (OER) performance. Figure 10 As shown, 10mA / cm 2The corresponding overpotential is 221 mV. Electrochemical stability is as follows: Figure 11 As shown, in acidic medium, 100 mA / cm 2 At a current density of [value], the potential can remain stable for about 50 hours.

[0073] The embodiments of the present invention have been described in detail above, but the content described is only a preferred embodiment of the present invention and should not be considered as limiting the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the patent coverage of the present invention.

Claims

1. A method for preparing an iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst, characterized in that: The steps are as follows: Step 1: Mix the ruthenium source solution with the morphology modifier and stir until homogeneous to obtain a precursor mixture solution; Step 2: Place the precursor mixture solution in a reaction vessel for hydrothermal reaction. After the reaction is completed, separate and dry to obtain ruthenium dioxide powder; Step 3: Prepare ruthenium dioxide powder to form solution A, slowly add iridium source solution dropwise into solution A, stir at constant temperature, centrifuge and dry to obtain iridium-loaded ruthenium dioxide powder; Step 4: Iridium-supported ruthenium dioxide powder is placed in an oxidizing atmosphere for heat treatment, and after cooling, iridium-doped ruthenium dioxide electrocatalyst is obtained.

2. The method for preparing iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: The morphology modifier is one of polyethylene glycol, polyvinylpyrrolidone, and citric acid, and the molar ratio of ruthenium to the morphology modifier is 1:5 to 5:

1.

3. The method for preparing iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst according to claim 2, characterized in that: The pH of the precursor mixture solution is adjusted to 7-9 using an alkaline solution; the alkaline solution is one of potassium hydroxide, sodium hydroxide, potassium carbonate, or ammonia water.

4. The method for preparing iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step two, the hydrothermal reaction temperature is 100~200℃, and the reaction time is 1~24h; In step three, the constant temperature stirring is carried out in a water bath or oil bath at 40~80℃ for 1~24 hours.

5. The method for preparing iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step four, the heat treatment temperature is 200~500℃, and the treatment time is 0.5~4h.

6. The method for preparing iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst according to any one of claims 1-5, characterized in that: The ruthenium source is one of ruthenium trichloride, ruthenium nitrate, and ruthenium acetate, and the concentration of the ruthenium source solution is 0.001~0.01 mol / L; the iridium source is one of chloroiridic acid, iridium nitrate, and iridium tetrachloride, and the concentration of the iridium source solution is 0~0.1 mol / L; the iridium doping ratio is 1~10 wt% of the mass of ruthenium dioxide.

7. The iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst prepared by the method described in any one of claims 1-6.

8. The iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst according to claim 7, characterized in that: It has a rutile structure.

9. The application of the iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst according to claim 7 or 8 in acidic water electrolysis for oxygen evolution.

10. The application according to claim 9, characterized in that: Iridium-doped ruthenium dioxide acidic oxygen evolution electrocatalyst was used as the anode electrode for acidic water electrolysis.